Lipid Composition of Thermophilic Geobacillus Sp. Strain gwe1 Isolated from Sterilization Oven - Blamey-Alegria, J (Elsevier Ireland Ltd, 2014)
GWE1 strain is an example of anthropogenic thermophilic bacterium, recently isolated from dark crusty material from sterilization ovens by Correa-Llantén et al. (Kor. J. Microb. Biotechnol. 2013. 41(3):278-283). Thermostability is likely to arise from the adaptation of macromolecules such as proteins, lipids and nucleic acids. Complex lipid arrangement and/or type in the cell membrane are known to affect thermostability of microorganisms and efforts were made to understand the chemical nature of the polar lipids of membrane. In this work, we extracted total lipids from GWE1 cell membrane, separated them by TLC into various fractions and characterize the lipid structures of certain fractions with analytical tools such as 1H, 13C, 31P and 2D NMR spectroscopy, ATR-FTIR spectroscopy and MSn spectrometry. We were able to identify glycerophosphoethanolamine, glycerophosphate, glycerophosphocholine, glycerophosphoglycerol and cardiolipin lipid classes and an unknown glycerophospholipid class with novel MS/MS spectra pattern. We have also noticed the presence of saturated iso-branched fatty acids with NMR spectra in individual lipid classes. © 2014 Elsevier Ireland Ltd.